THE SLOAN-C PILLARS AND BOUNDARY OBJECTS AS A FRAMEWORK FOR EVALUATING BLENDED LEARNING - Laumakis, Mark; Graham, Charles; Dziuban, Chuck (Online Learning, 2009)
The authors contend that blended learning represents a boundary object; a construct that brings together constituencies from a variety of backgrounds with each of these cohorts defining the object somewhat differently. The Sloan-C Pillars (learning effectiveness, access, cost effectiveness, student satisfaction, and faculty satisfaction) provide a foundation for the evaluation of asynchronous learning networks that works equally well for the evaluation of blended learning environments. The Pillars and a simplified model of a learning system, focus on inputs, processes, and outputs, and provide the framework for a case study of blended learning design and evaluation in a 500-student section of an Introductory Psychology course. Results of a multi-method evaluation of this course indicated very high levels of both learning effectiveness and student satisfaction. The article concludes with the suggestion that blended learning may represent a black swan, a high-impact, unpredicted, and rare event that highlights the limitations of our ability to reliably predict the future in any arena, including online learning environments.